THE SPIRITUAL IMPACT OF THE DHIKR ATTAQOH AS A LIVING QUR’AN PHENOMENON IN KARANGDUREN - Ihwan Agustono (LP2M IAI Miftahul Ulum Pamekasan, 2024)
Although it is in our nature to worship Allah, most people either forget to do so or choose not to for a variety of reasons, including being preoccupied with other priorities. Karangduren Village residents read Surah al-Ikhlas, the Attaqoh dhikr, 100,000 times in an effort to preserve their belief in Allah. In addition to examining the history of reading and application, this article aims to understand the impact of Attaqoh dhikr on the spiritual well-being of the residents of Karangduren village. This research takes a qualitative approach, including methods such as observation, interviews, and documentation. For data processing, data reduction methods, data presentation, and conclusion phases have been employed. This study discovered two forms of Attaqoh Dhikr in Krangduren village: independent dhikr and congregational dhikr. Independent dhikr is more flexible, whereas congregational dhikr takes place every two weeks on Tuesday evenings at the al-Huda mosque. Second, the personal and societal impact of reciting Attaqoh dhikr is increased peace of mind, the emergence of a sense of trust, satisfaction, and sincerity, and the spirituality of individuals. Dhikr Attaqoh in Karangduren village has succeeded in strengthening the spiritual condition of the community.